Krishna
0

Step 1:  Recall the "Law of Cosines"

            triangle angles A,B,C and sides a,b,c

            NOTE:ab and c are sides.

C is the angle opposite side c

The Law of Cosines (also called the Cosine Rule) says:

c^2 = a^2 + b^2 - 2ab cos (C)

\cos\left(C\right)=\frac{a^2+b^2\ -\ c^2}{2ab}


Step 2: Substitute the given measurements in the Cosine rule

            EXAMPLE: \cos\ C\ =\ \frac{8^{2\ }+\ 6^2\ -\ 7^2}{2\cdot8\cdot6}


Step 3: Do some calculations

          EXAMPLE: \cos\ C\ =\frac{\ 64\ +\ 36\ -\ 49\ }{96}\ =\ \frac{51}{96}

                                Cos C = 0.5312


Step 4: Send the Cos to R.H.S side.

            NOTE: Calculate the Cos inverse value.

                      EXAMPLE: C = \cos^{-1}\ \left(0.5312\right)

                                        C = 57.9 \degree